Hubungan Pemberian Pekerjaan Rumah (Pr) Dan Peran Orang Tua Di Rumah Dengan Hasil Belajar Peserta Didik Kelas III Sekolah Dasar - Rasyiqa, Dhaifina; Disurya, Ramanata; Imansyah, Farizal (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The formulation of the problem in this study is: is there a relationship between giving homework (pr) and the learning outcomes of grade III elementary school students, is there a relationship between giving the role of parents at home and the learning outcomes of grade III elementary school students, and is there a relationship between the relationship between giving homework (pr) and the role of parents at home with the learning outcomes of grade III elementary school students. The purpose of this study was to determine the relationship between giving homework (pr) and the learning outcomes of grade III elementary school students, to determine the role of parents at home with the learning outcomes of grade III elementary school students and to determine the relationship between giving homework (pr) and the role of parents at home with the learning outcomes of grade III elementary school students. The method used in this study is correlation research with a quantitative approach. Data collection techniques in this study used questionnaires, tests and documentation, while data analysis techniques used descriptive analysis, normality tests, multiple linear regression correlations, F tests, Determinant Coefficient Tests. Based on the results of the study, it shows that there is a significant relationship between Giving Homework (PR) and the Role of Parents at Home with the Learning Outcomes of Grade III Elementary School Students. Because, the results of the multiple correlation calculation at a strong correlation level of 0.662. The F test for N = 56 with a significance level of 5% (df = N-2) obtained a result of 20.67 > 3.52, this result indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Meanwhile, the contribution of the Relationship between Homework (pr) and the Role of Parents at Home with the Learning Outcomes of Grade III Elementary School Students is 44%.